Contemporary Art, Criminal Acts and Media Events. (2nd April 2016) - Dahlgren, Anna
Summary: Artworks that trespass legal bounds and are judged as illegal acts or objects are illuminating examples of how the notion of art is continuously negotiated by different agents in different contexts. This essay seeks to discuss news media as one such agent or context. The two cases considered are the media coverage of Dan Wolgers' participation in the exhibition Ecce Homo in Stockholm in 1992 and Anna Odell's project "Unknown woman 2009-349701" from 2009. Both acts were simultaneously considered as artistic statements and real illegal deeds. The overall aim is to explore how mass media – that is daily press, professional journals and television – interpreted this duality and how the media discourse intervened and acted in the artistic and legal processes. Thus, this article seeks to analyse the mediatization of art. Accordingly, this study expands its focus beyond the typical agents of the art world such as curators, critics and art historians as it also includes statements and writings from representatives of politics, media, entertainment, law and the general public. Although these artists and artworks differ in many respects, they share a legal postlude as well as extensive media coverage. The media debates that followed the production and display of these two artworks clearly impacted their legal postlude. Moreover, they directly or indirectly constituted parts of the artists' oeuvres. Being controversial acts, they allowed for multiple interpretations and thereby smoothly fed into the logic of the media system. Furthermore, these examples clearly display how individual artists and artworks may serve as vehicles in larger aesthetic and art political controversies within the logic and system of media.